Queer criminology, critique, and the "art of not being governed" - Ball, Matthew (Critical criminology, 2014)
This article builds on previous work that argues that a useful path for a "queer/ed criminology" to follow is one that takes "queer" to denote a position. It suggests that one way of developing such an approach is to adopt a particular understanding of critique - specifically one that draws from Michel Foucault’s view of critique as "the art of not being governed." It then charts some of the possible directions for such a "queer/ed criminology." While such an approach to critique has previously been discussed within critical criminologies, this article suggests that it is useful for queer criminologists to explore the opportunities that it affords, particularly in order to better appreciate how "queer/ed criminology" might connect to, draw from, or push against other currents among critical criminologies, and help to delineate the unique contribution that this kind of "queer/ed criminology" might make.